Flashing in-curb LEDs and beacons at unsignalized crosswalks and driver's visual attention to pedestrians during nighttime. Issue 3 (4th March 2021) - Lantieri, Claudio; Costa, Marco; Vignali, Valeria; Acerra, Ennia Mariapaola; Marchetti, Pierclaudio; Simone, Andrea
Abstract: Driver's visual attention (eye movements) and driving behaviour (kinematic data) were assessed when approaching an experimental crosswalk that included flashing white in-curb LED strips, flashing orange beacons, backlit 'Yield here to pedestrians' vertical signs, and enhanced lighting when a staged pedestrian attempted to cross. An experimental condition in which all devices were active was compared with a control condition in which only enhanced lighting and backlit vertical signs were active. The results showed a significant increase of motorists' yielding compliance, distance of first fixation to the pedestrian area, standard deviation for horizontal eye movements in the experimental condition. The introduction of flashing in-curb LED strips and flashing orange beacons proved to be very effective in increasing the night-time safety of the pedestrian crossing. Practitioner summary: The study investigated the effects of flashing in-curb LED strips and beacons on driver's visual attention (eye movements) and speed when approaching a crosswalk during night-time. The results showed that the combination of these flashing devices significantly increased yielding compliance and the distance of pedestrian detection. Abbreviations: ANOVA: analysis of variance; EU: European Union; HAWK: high intensity activated crosswalk system; LED: light-emitting diode; PHB: pedestrian hybrid beacons; ROI: region of interest; RRFB: rectangular rapid flashing beacons; UK: United Kingdom; US: United States